SMART ASSISTANCE PUBLIC TRANSPORT SYSTEM - MISS.NANAWARE SONALI M.,; PROF.MANTRI D.B., (International Journal of Innovations in Engineering Research and Technology, 2021)
Present paper is an attempt to provide research knowledge found during experimentation on public city bus transportation system in India. The paper discussesand reviewsthe major transportation problems associated with city bus transportation in various cities of India.A special hardware and software has been designed to solve these problems. The motto behind this research was to create a system that is easy to assist the transportation system and that can be adaptable to user-friendly smart phones. The solution provided here is cost-effective as per the data obtained states.